Attenuation Correction Effects in Rainfall Estimation at X-Band Dual-Polarization Radar: Evaluation with a Dense Rain Gauge Network. (20th June 2016) - Oh, Young-A; Lee, DaeHyung; Jung, Sung-Hwa; Nam, Kyung-Yeub; Lee, GyuWon
Abstract : The effects of attenuation correction in rainfall estimation with X-band dual-polarization radar were investigated with a dense rain gauge network. The calibration bias in reflectivity (Z H ) was corrected using a self-consistency principle. The attenuation correction ofZ H and the differential reflectivity (Z D R ) were performed by a path integration method. After attenuation correction, Z H andZ D R were significantly improved, and their scatter plots matched well with the theoretical relationship betweenZ H andZ D R . The comparisons between the radar rainfall estimation and the rain gauge rainfall were investigated using the bulk statistics with different temporal accumulations and spatial averages. The bias significantly improves from 70% to 0% withR ( Z H ) . However, the improvement withR ( Z H, Z D R ) was relatively small, from 3% to 1%. This indicated that rainfall estimation using a polarimetric variable was more robust at attenuation than was a single polarimetric variable method. The bias did not show improvement in comparisons between the temporal accumulations or the spatial averages in either rainfall estimation method. However, the random error improved from 68% to 25% with different temporal accumulations or spatial averages. This result indicates that temporal accumulation or spatial average (aggregation) is important to reduce random error.